Pulmonary Peripheral Carcinoids after Diffuse Idiopathic Pulmonary Neuroendocrine Cell Hyperplasia and Tumorlets: Report of 3 Cases - Carlos Abrantes; Rui Caetano Oliveira; Joana Saraiva; João Bernardo; Lina Carvalho (Case Reports in Pulmonology)
Diffuse idiopathic pulmonary neuroendocrine cell hyperplasia (DIPNECH) and tumorlets are neuroendocrine cells proliferations smaller than 5 mm. The former confines to bronchial/bronchiolar wall, while the latter broke through epithelial basement membrane. The authors present 3 cases of DIPNECH and tumorlets associated with a typical peripheral carcinoid tumor without underlying lung disease. The patients presented with nonspecific pulmonary symptoms: 3 females, 60, 72, and 84 years old, whose CT-scans showed well-defined pulmonary nodules, 2.2, 1.6, and 1.4 cm, respectively; first patient was submitted to lobectomy and the others underwent surgical biopsy. Whitish/brownish lobulated tumors corresponded to typical carcinoids (less than 2 mitoses/2 mm2 and without necrosis); polygonal/elongated cells under lobular pattern expressed CD56, chromogranin A, synaptophysin, and CK7; Ki-67 positivity was between 1 and 3%. Bronchial/bronchiolar wall neuroendocrine cell hyperplasia and several neuroendocrine nodules under 5 mm, with identical morphologic and immunoexpression, were observed, without lung disease. Typical carcinoid associated with DIPNECH and tumorlets without other pulmonary diseases is rare. Sporadic cases may recall embryonal neuroendocrine differentiation potentiality to develop peripheral hyperplasia, most commonly in underoxygenated parenchyma. The described cases are elucidative of peripheral spectrum of neuroendocrine cell tumour evolution, reinforcing higher female incidence as in central carcinoids, still without a clear preneoplastic lesion.